Continuation of twins across grain boundary in extruded Mg-3Al-1Zn alloy. (1st September 2013) - Xu, S; Liu, T M; Zhang, Y; He, J J; Zeng, W; Wang, J X
Abstract : Paired twins in an extruded Mg-3Al-1Zn alloy are investigated by using electron backscattered diffraction in the current paper. The results show that these paired twins are discovered at low misorientation grain boundaries. The twin variant (1-102)[−1101] is operated in the paired twins. Additionally, a macroscopic angle exists in the paired twins and is determined by the c axis misorientation of the grains.